Magnitude of Neonatal Jaundice and Its Associated Factor in Neonatal Intensive Care Units of Mekelle City Public Hospitals, Northern Ethiopia - Eyasu A. Lake; Gerezgiher B. Abera; Gedion A. Azeze; Natnaeal A. Gebeyew; Birhanu W. Demissie (Hindawi Limited, 2019)
Background. Jaundice in the neonate is one of the most common clinical problems. Globally, every year about 1.1 million babies develop it and the vast majority reside in sub-Saharan Africa and South Asia. Study on magnitude and local factors associated with neonatal jaundice is limited in Ethiopia. So this study was aimed at assessing magnitude and predictors of neonatal jaundice among neonates admitted to neonatal intensive care unit of public hospitals in Mekelle city, Northern Ethiopia. Methods. Institution based cross-sectional study was conducted from February to April 2016 in neonatal intensive care unit of Mekelle city public hospitals. Systematic random sampling technique was used to select study participants. Data was collected by interviewing mothers through structured questionnaire and reviewing neonates' medical records using checklist. Multivariable binary logistic regression analyses were employed to identify factors associated with neonatal jaundice. Results. A total of 209 neonates with their mothers were included. The proportion of neonatal jaundice was found to be 37.3%. Prolonged labor [AOR = 4.39; 95% CI (1.8-10.69)], being male [AOR = 3.7; 95% CI (1.54-8.87)], maternal "O" blood group [AOR = 5.05; 95% CI (1.53-16.72)], sepsis [AOR = 2.64; 95% CI (1.15-6.05)], and blood type incompatibility [AOR = 18.21; 95% CI (6.36-52.13)] were positively associated with neonatal jaundice while night time delivery [AOR 0.42; 95% CI (0.18-0.96)] showed negative association. Conclusion. The magnitude of neonatal jaundice among neonates was found to be high. Duration of labor, time of delivery, sexes of neonate, sepsis, maternal blood group, and blood type incompatibility were significantly associated with neonatal jaundice. Therefore, improving newborn care and timely intervention for neonates with ABO/Rh incompatibility are recommended.